Harnessing psychoanalytical methods for a phenomenological neuroscience - Cusumano, Emma P.; Raz, Amir (Frontiers in Psychology, 2014)
Analysis may offer valuable methods for bridging the gap between first-person and third-person accounts of the mind. Using both systematic observational approaches and unstructured narrative interactions, psychoanalysts help patients articulate their experience and bring unconscious mental contents into awareness. Similar to seasoned meditators or phenomenologists, individuals who have undergone analysis are experts in discerning and describing their subjective experience, making them ideal neurophenomenology participants. Moreover, analytic techniques may provide a means of guiding untrained experimental participants to greater awareness of their mental continuum, as well as gathering subjective reports about fundamental yet elusive aspects of experience including selfhood, temporality, and inter-subjectivity. Mining psychoanlysis for its methodological innovations would offer a fresh turn for neuropsychoanalysis and cognitive science as a whole – showcasing the integrity of analysis alongside the irreducibility of human experience.